2019
DOI: 10.21470/1678-9741-2018-0261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Creatinine Levels on Mortality after Coronary Artery Bypass Grafting Surgery: an Observational Study

Abstract: Introduction Renal function is an independent risk factor for mortality among on-pump coronary bypass grafting (ONCABG) patients. This association is well known in the international literature, but there is a lack of knowledge of how admission creatinine (AC) levels modulate each cardiovascular risk factor. Objective The aim of this paper was to assess the effect of different AC levels on mortality among ONCABG patients. Methods 1,599 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…WBC play an essential role in cardiovascular disease, some studies have found elevated WBC was associated with cardiovascular complications and mortality in patients after CABG [ 29 , 32 ]. Creatinine increased during perioperative stage served as independent risk factor for mortality in patients after CABG, and some risk assessment models after cardiac surgery included creatinine [ 6 , 20 , 33 , 34 ]. SpO 2 as an earlier warning index of hypoxemia is very important prognostic factor for critically ill patients with cardiovascular disease [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…WBC play an essential role in cardiovascular disease, some studies have found elevated WBC was associated with cardiovascular complications and mortality in patients after CABG [ 29 , 32 ]. Creatinine increased during perioperative stage served as independent risk factor for mortality in patients after CABG, and some risk assessment models after cardiac surgery included creatinine [ 6 , 20 , 33 , 34 ]. SpO 2 as an earlier warning index of hypoxemia is very important prognostic factor for critically ill patients with cardiovascular disease [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A worse prognosis may result from the combination of some risk factors and higher admission creatinine values. Moreover, lower admission creatinine values have been linked with a protective impact, even among elderly patients and those with a high cardiopulmonary bypass time [29].…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%